2003
DOI: 10.1021/ef030102l
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Styrene Recovery from the Pyrolysis of Waste Expandable Polystyrene

Abstract: Catalytic and thermal degradation of waste expandable polystyrene (WEPS) have been studied in a semi-batch reactor with continuous flow of nitrogen to achieve greater oil yield and maximize styrene monomer recovery. Effect of temperature, nature of catalyst and its size, reaction time of catalytic pyrolysis, and effect of repyrolysis have been also investigated. Higher reaction temperature favors the oil yield and also decreases the reaction time with maximum styrene selectivity (76.31 wt %) at 450 °C. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Although the dimer yield is not highly affected by temperature, an increase in temperature from 450°C to 550°C leads to a reduction in the formation of the dimer, thus increasing the formation of lower molecular weight compounds, but an increase from 550°C to 600°C gives way to the formation of the dimer. Park et al (2003) observed the same trend, although it is not very pronounced, for the yield of styrene dimer with temperature, i.e., it slightly decreases from 9.5 wt% at 400°C to 8.8 wt% at 450°C and increases to 9.5 wt% when temperature is increased to 480°C.…”
Section: Effect Of Temperaturesupporting
confidence: 59%
See 2 more Smart Citations
“…Although the dimer yield is not highly affected by temperature, an increase in temperature from 450°C to 550°C leads to a reduction in the formation of the dimer, thus increasing the formation of lower molecular weight compounds, but an increase from 550°C to 600°C gives way to the formation of the dimer. Park et al (2003) observed the same trend, although it is not very pronounced, for the yield of styrene dimer with temperature, i.e., it slightly decreases from 9.5 wt% at 400°C to 8.8 wt% at 450°C and increases to 9.5 wt% when temperature is increased to 480°C.…”
Section: Effect Of Temperaturesupporting
confidence: 59%
“…They obtained a styrene yield of 78 wt% at this temperature. Park et al (2003) reported a styrene yield of around 70 wt% at 450°C in a batch thermal reactor, but the yield was considerably higher when BaO or ZnO catalysts were used. Chauhan et al (2008) operated in a fixed bed reactor from 350 to 500°C under vacuum conditions, and they obtained a styrene yield higher than 80 wt% at 500°C.…”
Section: Effect Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…PS can be depolymerized to monomer styrene, which can be polymerized to polystyrene again and be widely used to synthesize other chemicals. It is known that waste PS can be converted into styrene by simple thermal degradation [4][5][6][7][8][9], but the temperature is too high such as 873K. By using suitable catalysts, the degradation temperature can be lowered with a higher yield of styrene monomer.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…In PS pyrolysis, the yield of low-molecular-weight mononuclear aromatic compounds exceeds 95%. Therefore, this process is actively studied as a method for recirculation of the waste polymer [3].The yields and composition of PS pyrolysis products depend on the temperature, presence of catalysts and solvents, type and design of the reactor, and other process conditions [3][4][5][6][7][8][9]. Performing the polymer pyrolysis in solvents allows the conditions of mass and heat transfer in the reaction medium to be improved (otherwise these conditions are unfavorable because of high viscosity of polymer melts) and the process temperature to be decreased [9][10][11].…”
mentioning
confidence: 99%